THE IMPORTANCE OF THE DEVELOPMENT OF CREATIVE ABILITIES IN STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2009)
The article is dedicated to review and substantiation of the importance of creativity development for the students of pedagogical universities. The author pays special attention to students' creative abilities considering them as a driving force for the personal creative potential enhancement, development of students' ability to treat reality creatively, to solve practical tasks independently, to be ready for self-improvement and self-education.
Keywords: creative personality; creativity; future teachers